Governança democrática dos recursos hídricos na região metropolitana de São Paulo: propostas a partir da experiência da região metropolitana de Buenos Aires - Fantin, Adriana Aghinoni (2015)
The metropolitan area of São Paulo (RMSP) is in a deep crisis of its water resources, which sets out the current governance weaknesses, and invites us to a reflection of the critical nodes that prevent a more effective service. This work deepens the governance, management and the current sanitation situation, based on the expertise of the Metropolitan Area of Buenos Aires, which experienced severe crisis in water and sanitation coverage, as well as contamination of watersheds. Within a privatization process that has exacerbated the water crisis, the option for the metropolitan area of Buenos Aires was the re-nationalization, and the quest for democratic governance, involving several federation entities. The main difference is the introduction of a planning agency, in which the federal, provincial one, the City of Buenos Aires and all the municipalities in the metropolitan region, jointly deliberate priority projects, linking the company providing the service. Moreover, the experience of the Matanza Riachuelo Basin Management presents collegial governance by federal entities and has multidisciplinary expertise, overcoming obstacles resulting from governmental and intergovernmental arrangements to cope with the complexity of managing the basin. It is proposed at the end, an improvement plan for the management of water resources, with short proposals, medium and long term. As a short term measure suggests the creation of a Metropolitan Water Agency in order to plan and implement public policies aimed at coping the water problem, breaking the inertia of federal entities across the water crisis, with collegiate decision-making body, Members municipalities, state and civil society in constant search for solutions of common interest, whose decisions binding upon it the company which supplies the service. In the medium term, it is recommended public discussion of the utility business model in addition to the review of planning and resource allocation actions made by SABESP. Finally, as a long term measure, it is essential drawing up a Master Plan Metropolitan jointly look after capture measures, treatment, and water and sewage coverage, and that promotes environmental sustainability and integration of municipalities to better use of urban space. The adoption of a democratic governance for water issue in the RMSP will provide a possible scenario for the necessary changes within the RMSP in water resources management. Society must be largely responsible for the fate of the water and should not noble mission be undertaken by those interested in turning it into a good private consumption.